2001
DOI: 10.1111/j.1095-8649.2001.tb02286.x
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization dynamics in sockeye salmon and a comparison of sperm from alternative male phenotypes

Abstract: Sockeye salmon Oncorhynchus nerka sperm maintained high fertility for 10 s after being exposed to water but fertility dropped sharply after that. Eggs also showed limited longevity after being immersed in water, with a large drop in fertility occurring after 20 s of exposure to water. The association between eggs and sperm occurs very rapidly. 80% fertilization success was achieved with 5 s of sperm-egg mixing and c. 25% was achieved with <0·5 s of sperm-egg mixing. Sperm from different male age classes differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(55 citation statements)
references
References 39 publications
3
49
3
Order By: Relevance
“…The overall confinement stress on both captive groups probably contributed to delayed maturation, higher egg retention rates, and especially depressed overall fertilization success compared with natal fish. The mean egg survival from captive fish (56%) were lower than eggs from natal spawners (88%) and published values for wild sockeye salmon (>90%)(Hoysak & Liley, 2001; Galbraith, 2003). Campbell et al .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The overall confinement stress on both captive groups probably contributed to delayed maturation, higher egg retention rates, and especially depressed overall fertilization success compared with natal fish. The mean egg survival from captive fish (56%) were lower than eggs from natal spawners (88%) and published values for wild sockeye salmon (>90%)(Hoysak & Liley, 2001; Galbraith, 2003). Campbell et al .…”
Section: Discussionmentioning
confidence: 66%
“…Consistent with other research, there were larger differences in viability among eggs from different females than among milt from different males (Nagler et al ., 2000; Hoysak & Liley, 2001). This individual variability was not correlated with any of the morphological, physiological or reproductive variables recorded from each parent.…”
Section: Discussionmentioning
confidence: 99%
“…Eggs are fertilized after a sperm cell enters the micropyle, which is barely wide enough to allow entry of one sperm cell (Ginsburg, 1963;Kobayashi and Yamamoto, 1981;Yanagimachi et al, 1992). Thus, in salmonids, where up to 80% of the eggs can be fertilized within the first 5 s of egg and sperm interactions (Hoysak and Liley, 2001), the first sperm cell to enter the micropyle fertilizes the egg (Kobayashi and Yamamoto, 1981;Yanagimachi et al, 1992). These female evolved characteristics may help enforce FIGURE 4 | The effect of relative motility PCA (i.e., per cent motile sperm cells and sperm velocity in ovarian fluid) and relative number of sperm cells on proportion of larvae sired for subdominant males ejaculating after the competing dominant male (asynchrony).…”
Section: Discussionmentioning
confidence: 99%
“…For example, eggs of the rainbow trout Oncorhynchus mykiss, and sockeye salmon Oncorhynchus nerka, lost their fertilizing capacity after 40 s (Hoysak and Liley, 2001;Liley et al, 2002). It has been shown that higher osmolality (up to 200 mOsm kg À1 ) significantly prolonged the period of time (up to 6 min) during which the eggs of this species retained their fertilization capability, as compared to eggs activated with freshwater (0 mOsm kg À1 ), where most eggs were incapable of fertilization after 60 s. Published data already suggested that duration of the ability of eggs to be fertilized is species-dependent.…”
Section: Discussionmentioning
confidence: 99%